From passion to practice: clinician teachers’ insights on family medicine obstetrical care - Sabrina Kolker; Anne Biringer; Joyce Nyhof-Young; Cynthia Whitehead; Sahana Kukan; Jessica Bytautas; June Carroll (Canadian Medical Education Journal)
Background: Declining numbers of family physicians (FPs) provide obstetrical care - an essential service. Exploring reasons why current family medicine obstetrics (FM-OB) clinician teachers chose this field and what motivates them to continue may inform retention strategies and inspire future family medicine learners. Our objective was to explore perspectives of academic FPs who practice FM-OB with the goal of informing recruitment of future FM-OB practitioners and retention of those currently practicing FM-OB.